9(l+2)=3(l-3)

Simple and best practice solution for 9(l+2)=3(l-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(l+2)=3(l-3) equation:


Simplifying
9(l + 2) = 3(l + -3)

Reorder the terms:
9(2 + l) = 3(l + -3)
(2 * 9 + l * 9) = 3(l + -3)
(18 + 9l) = 3(l + -3)

Reorder the terms:
18 + 9l = 3(-3 + l)
18 + 9l = (-3 * 3 + l * 3)
18 + 9l = (-9 + 3l)

Solving
18 + 9l = -9 + 3l

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-3l' to each side of the equation.
18 + 9l + -3l = -9 + 3l + -3l

Combine like terms: 9l + -3l = 6l
18 + 6l = -9 + 3l + -3l

Combine like terms: 3l + -3l = 0
18 + 6l = -9 + 0
18 + 6l = -9

Add '-18' to each side of the equation.
18 + -18 + 6l = -9 + -18

Combine like terms: 18 + -18 = 0
0 + 6l = -9 + -18
6l = -9 + -18

Combine like terms: -9 + -18 = -27
6l = -27

Divide each side by '6'.
l = -4.5

Simplifying
l = -4.5

See similar equations:

| 2x+3(10-x)=25 | | 8+2x=7x-2 | | 15x+73=-347 | | 2(4x-5)-3(-x+6)=2/5(15x-65) | | 8x-12+4=8x-8 | | -5+7x=-4x+39 | | 3x+15+5x=-1 | | 3d^2+7d-6=0 | | 2y=3y-15 | | -3n(4b)+2a(3b)= | | 10x-9=2x-69 | | 8(2x+1)=4x-6x | | 12-6x=5-3+15x | | -5x-5=-5x | | 3(2x-5)=-39 | | 14+2x=-9-5x+4x | | 7g=49 | | y=-1/4+1 | | 3(x+3)=8x+6-5x+3 | | 9-9x=173-37x | | -2/5= | | 3x-12=4x-9 | | 5(2-y)+7y=-3(y+5) | | 3x+8=116 | | -3x+5=-3x+4 | | -3*-4*4-4*-4*-2= | | x-8=-51 | | 4y-7=3-2(9y-15) | | -6x-33=-3x-27 | | .35x+.20(240-x)=57 | | -3x-25=4(x-1) | | 8x^3-20x^2-2x+5=0 |

Equations solver categories